2022
DOI: 10.1007/s15010-022-01768-0
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year retrospective analysis of the prognostic value of MqSOFA compared to lactate, NEWS and qSOFA in patients with sepsis

Abstract: Purpose Sepsis is a life-threating organ dysfunction caused by a dysregulated host response to infection. Being a time-dependent condition, the present study aims to compare a recently established score, i.e., modified quick SOFA (MqSOFA), with other existing tools commonly applied to predict in-hospital mortality. Methods All cases of sepsis and septic shock consecutively observed at St. Anna University Hospital of Ferrara, Italy, from January 2017 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Also, after Bonferroni’s correction, MqSOFA outperformed qSOFA in respiratory and urinary etiologies. 28 Another study determined the detection rate of PCT, sequential organ failure assessment (SOFA), and qSOFA in estimating sepsis and in-hospital mortality in 65-year-old patients referred to the ED. It was found that the PCT test possesses a higher prognostic and predictive capacity for the diagnosis of sepsis than qSOFA and SOFA, with AUC = 0.883 at 95% confidence interval (CI): 0.835–0.931 and p < 0.0001.…”
Section: Resultsmentioning
confidence: 99%
“…Also, after Bonferroni’s correction, MqSOFA outperformed qSOFA in respiratory and urinary etiologies. 28 Another study determined the detection rate of PCT, sequential organ failure assessment (SOFA), and qSOFA in estimating sepsis and in-hospital mortality in 65-year-old patients referred to the ED. It was found that the PCT test possesses a higher prognostic and predictive capacity for the diagnosis of sepsis than qSOFA and SOFA, with AUC = 0.883 at 95% confidence interval (CI): 0.835–0.931 and p < 0.0001.…”
Section: Resultsmentioning
confidence: 99%
“…We verified by LASSO and multifactorial logistic regression that an increase in RDW was also significantly associated with the development of SALI ( P < 0.001). Lactate is a reliable biomarker for predicting organ failure and death in sepsis patients [25,26] . Increased lactate production in sepsis due to enhanced glycolysis, altered pyruvate dehydrogenase activity, and other factors [27] .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that qSOFA is a rapid screen for predictors of mortality rather than a means to identify sepsis specifically and has limited prognostic utility in human studies. [97][98][99] Several studies have evaluated modified qSOFA criteria in dogs with variable results. In a critically ill population of dogs, qSOFA was not predictive of mortality in contrast to plasma lactate concentration, but that population had few dogs with sepsis.…”
Section: Organ System Scorementioning
confidence: 99%
“…To identify organ dysfunction, the qSOFA score requires 2 or more of altered mentation (a diminished Glasgow Coma Scale score), hypotension (systolic blood pressure ≤100 mm Hg), or tachypnea (respiratory rate ≥22/min). It should be noted that qSOFA is a rapid screen for predictors of mortality rather than a means to identify sepsis specifically and has limited prognostic utility in human studies 97–99 . Several studies have evaluated modified qSOFA criteria in dogs with variable results.…”
Section: Sepsis‐3 (Society Of Critical Care Medicine European Society...mentioning
confidence: 99%